Economic backwardness in historical perspective : a book of essays - Gerschenkron, Alexander (Cambridge, Massachusetts : Belknap Press of Harvard University Press, 1962)
Edited collection uses a history of economic thought perspective to explore the evolving role of Latin America within the context of globalization. In particular, it examines the region's resilience in the face of the global financial crisis. Economic Development and Global Crisis explains that Latin America is a region with distinct characteristics and peculiarities which have been shaped from the colonial era up to the present day. The contributions suggest that several features which were perceived as economic backwardness have turned out to be advantageous, and this may explain why Latin America is withstanding the crisis much better than Europe, Japan and the USA. This book will be of interest to scholars working in the areas of economic development, economic history, the history of economic thought and Latin American studies.
Includes bibliographical references and index.
aia 10/05/2018
Loans
Keywords: Industries; Industrialization $1 (BEurope $1 (BHistory $1 (B19th century.s; Soviet Union